Kajian Yuridis Normatif Pertanggungjawaban Dokter atas Kesalahan Diagnosis dalam Pelayanan Medis yang Menyebabkan Kematian Pasien - Triyanto Agung Praptono Wibowo; Rina Arum Prastyanti; Zaenal Mustofa (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
The growing number of alleged medical malpractice cases in Indonesia, particularly physicians’ misdiagnosis resulting in patient death, underscores the need for stronger legal certainty and accountability in healthcare services. Physicians are professionally obligated to conduct diagnosis and medical treatment in accordance with professional standards, service standards, and standard operating procedures; however, negligence may occur and lead to severe harm. This study aims to analyze the legal provisions governing physicians’ liability for misdiagnosis causing patient death and to examine the forms of legal responsibility that may be imposed. The research applies a normative juridical method using a case approach and literature review, relying on primary legal materials such as the Indonesian Civil Code, the Criminal Code, the Medical Practice Law, the Hospital Law, and Law Number 17 of 2023 on Health, supported by secondary and tertiary sources. The findings indicate that physicians may be held liable under civil, criminal, and administrative law if the essential elements of medical negligence are proven, namely duty of care, breach of duty, harm (including death), and a causal relationship between the misdiagnosis and the fatal outcome. Moreover, liability may extend to hospitals under the doctrines of vicarious liability, hospital liability, and strict liability. This study implies the importance of strengthening professional competence, reinforcing disciplinary mechanisms, and ensuring balanced legal protection for both patients and healthcare professionals within Indonesia’s health law framework.